2012
DOI: 10.1111/j.1552-6569.2012.00765.x
|View full text |Cite
|
Sign up to set email alerts
|

Retropharyngeal Ganglioneuroma: A Case Report

Abstract: Ganglioneuromas are uncommon, benign, and highly differentiated tumors arising from sympathetic ganglia. Common sites for these tumors include the paraspinal region of the retroperitoneum and posterior mediastinum. We report a case of a retropharyngeal ganglioneuroma, a rare occurrence, emphasizing its key imaging characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
(15 reference statements)
1
4
0
Order By: Relevance
“…Increased signal intensity on T2W images is thought to reflect high cellularity and large interstitial volume 11. Linear hypointense striations within the lesion likely correspond to interlacing bundles of Schwann cells and collagen fibres 14. Apart from the calcifications, the imaging features of our case correlate well with those described in the literature.…”
Section: Discussionsupporting
confidence: 73%
“…Increased signal intensity on T2W images is thought to reflect high cellularity and large interstitial volume 11. Linear hypointense striations within the lesion likely correspond to interlacing bundles of Schwann cells and collagen fibres 14. Apart from the calcifications, the imaging features of our case correlate well with those described in the literature.…”
Section: Discussionsupporting
confidence: 73%
“…Generally, ganglioneuroma has been considered to occur mainly in children and young adults, and to be most commonly diagnosed between the mean ages of 5.5 to 10 years (4,12,13). However, recent reports suggest that the mean age at diagnosis is 40 to 50 years (2,5,(14)(15)(16)(17). GN is slightly more common in women than in men (1.13:1 to 1.5:1) (1, 4).…”
Section: Discussionmentioning
confidence: 97%
“…the retropharyngeal space as in the case described by Yang et al (1,2). Adrenal location of ganglioneuroma is rare: Linos and co-authors identified approximately 230 of such literature cases (3).…”
Section: Introductionmentioning
confidence: 82%
“…The biggest resected GN assessable through literature research up to now showed a maximum diameter of approximately 23 cm [6] in a 42-year-old patient located solely thoracically [6]. Located most commonly in the posterior mediastinum (41.5%) or retroperitoneally (37.5%), ganglioneuromas can be found in the adrenal glands (21%), in the neck (8%), retropharyngeally, or more rarely in the sella turcica [7][8][9][10]. Computed tomography (CT) or magnetic resonance imaging (MRI) represents the gold standard for diagnosis and estimation of tumor extent.…”
Section: Introductionmentioning
confidence: 98%